Changing Foreign Policy of the JDP in the Context of Turkish National Identity - Kancaal, Ipek; Rolenc, Jan Martin, 1980-; Hlavsová, Aneta, 1989-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Through the history of modern Turkey, three main ideological currents have been influential in determining the Turkish foreign policy. These are Westernism, Nationalism/Turkism and Islamism. Although Westernism has been prevailing national identity of Turkey until the end of the Cold War, Islamism and Nationalism have remained in the background without losing their weight. Until the collapse of the communist regime of the Soviet Union, Turkey had played a buffer role between the Soviet Union and the West, solely by remaining as an important ally of the United States as it became a part of the NATO in 1952. After the end of the Cold War, Turkey embarked on a quest to create alternative foreign policy roles to keep its essential position in the international politics. Since the Justice and Development Party (JDP) came to power in Turkey in 2002, its foreign policy paradigm remained uniquely different from the previous governments. Moreover, in each of its governmental term, the focus of the party has changed significantly; the first governmental term specifically focused on the full membership accession for the European Union, while the second governmental term between 2007-2011 mainly focused on Middle East policies. After the failure of the Davutoğlu Doctrine – neo-Ottomanism, the JDP sought for alternative foreign policy strategies especially after the attempted coup d’état in July 2016. These foreign policy changes were classified on different levels; some scholars observed paradigm shift while some others observed pragmatic program changes. In this thesis, these foreign policy changes are going to be examined through the typology of Charles Hermann’s foreign policy change model.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses